Recontacting biobank participants to collect lifestyle, behavioural and cognitive information via online questionnaires: lessons from a pilot study within FinnGen. Issue 10 (5th October 2022) - Rodosthenous, Rodosthenis S; Niemi, Mari E K; Kallio, Lila; Perala, Merja; Terho, Perttu; Knopp, Theresa; Punkka, Eero; Makkonen, Enni M; Nurmi, Paula; Makela, Johanna; Wihuri, Pauli; Hautalahti, Marco; et al.
Abstract : Objectives: To recontact biobank participants and collect cognitive, behavioural and lifestyle information via a secure online platform. Design: Biobank-based recontacting pilot study. Setting: Three Finnish biobanks (Helsinki, Auria, Tampere) recruiting participants from February 2021 to July 2021. Participants: All eligible invitees were enrolled in FinnGen by their biobanks (Helsinki, Auria, Tampere), had available genetic data and were >18 years old. Individuals with severe neuropsychiatric disease or cognitive or physical disabilities were excluded. Lastly, 5995 participants were selected based on their polygenic score for cognitive abilities and invited to the study. Among invitees, 1115 had successfully participated and completed the study questionnaire(s). Outcome measures: The primary outcome was the participation rate among study invitees. Secondary outcomes included questionnaire completion rate, quality of data collected and comparison of participation rate boosting strategies. Results: The overall participation rate was 18.6% among all invitees and 23.1% among individuals aged 18–69. A second reminder letter yielded an additional 9.7% participation rate in those who did not respond to the first invitation. Recontacting participants via an online healthcare portal yielded lower participation than recontacting via physical letter. The completion rate of the questionnaire and cognitive tests was high (92% and 85%, respectively), and measurements were overall reliable among participants. For example, the correlation (r) between self-reported body mass index and that collected by the biobanks was 0.92. Conclusion: In summary, this pilot suggests that recontacting FinnGen participants with the goal to collect a wide range of cognitive, behavioural and lifestyle information without additional engagement results in a low participation rate, but with reliable data. We suggest that such information be collected at enrolment, if possible, rather than via post hoc recontacting.